Development of an innovative mixed reality methodology for teaching medical students complex pathologies - Toledano, Ruan; Giordano, Cecília; Pozzebon, Eliane; Manzon, Josete (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais do XXVII Simpósio de Realidade Virtual e Aumentada, 2025)
The inclusion of mixed reality (MR) and other types of immersion technology into medical education has emerged as a transformative and innovative approach for teaching complex pathological concepts. This paper presents the methodological framework for developing an MR-based educational tool designed to enhance disease understanding through interactive three-dimensional models. The development process included bibliographic research, 3D modeling using Blender® and Substance 3D Painter®, animation techniques, and integration via Unity® onto mixed reality glasses. Preliminary classroom studies demonstrated comparable knowledge retention with improved spatial reasoning and engagement when using the proposed technology. Both groups showed significant learning gains after the intervention (p < 0.001); the control group improved from 52% to 69%, and the test group from 61% to 71%, with the latter achieving higher final scores and reduced score dispersion. The methodology also addresses key barriers to scalable MR implementation in education, providing a replicable approach for academic institutions. Furthermore, this study introduces a structured development pipeline that addresses technological challenges in MR content creation, such as anatomical fidelity, intuitive interaction, performance optimization, and collaborative use. The contribution extends beyond medical education, offering a replicable MR deployment framework relevant to the MR research communities.